Management of Pediatric and Adolescent Breast Masses - Kennedy, Raelene D.; Boughey, Judy C. (Seminars in Plastic Surgery, 2013)
Breast masses in children and adolescents are uncommon and most often benign. Occasionally, however, they require surgical intervention for lifestyle limiting symptoms or malignant potential. These masses are best evaluated with physical exam and ultrasound. Breast masses likely to be encountered by the surgeon in the pediatric and adolescent population include intraductal papillomas, phyllodes tumors, primary breast cancer, and metastatic lesions. Unlike adults, pediatric and adolescent breast cancer tends to be of the secretory variety and typically have less metastatic potential. However, cases of inflammatory and medullary breast cancers have also been reported in girls and appear more aggressive. Radiation exposure during breast development is a risk factor to subsequent development of breast cancer. Surgical objective for a concerning pediatric and adolescent breast mass is complete resection while preserving normal breast development, when appropriate. The need for routine axillary dissection for malignant cases in children appears unnecessary from the limited data available, and the authors favor sentinel lymph node sampling and reserve axillary dissection for positive lymph nodes.
Keywords: pediatric; breast cancer; phyllodes; intraductal papilloma; surgery